(untitled) (Jurnal Bahasa, 2008)
A neologism is a word, term or phrase which has been recently created (coined) - often used to apply to new concepts, to synthesize pre-existing concept, or to make older terminology sounds more contemporary. Neologism is especially useful in identifying inventions, new phenomena or old ideas which have taken on a new cultural context. Neologism can also refer to an existing word or phrase which has been assigned to a new meaning. Neologisms tend to occur more often in cultures which are rapidly changing, and also in situations where there is easy and fast propagation of information. Such new words often become popular by way of mass media such as television, the Internet, through word of mouth, e.g. academic discourse, political speech etc. Neologisms often become acceptable as part of the language. Other times, however they disappear from common usage. Whether a neologism continues as part of the language depends on many factors, the most important of which are probably acceptance by the public, acceptance by linguistic experts and incorporation into dictionaries. This paper focuses on neologism in German, Malay and Indonesian in terms of types and forms, its pragmatic values, word sources, and also other linguistic problems relating to neologism such as lexicalization and translating.